Dynamics of Islamic Legal Thought: Comparison of the Concept of Maqashid Al-sharī’ah in Madhhab Zaidiyah and Ja'fariyah - Khori, Ahmad; Setiawan, Setiawan; Said, Basnang; Qulyubi, M. Mujib (Universitas Muhammadiyah Surakarta, 2025)
The research paper analyzed the concept of Maqāṣid al-Sharī’ah in Zaidiyah and Ja’fariyah madhhabs comparison, examining its relevance in both fractured times and the modern world. The background for this research was the lack of a systematic study on the comparative epistemological and methodological characteristics of the two madhhabs of thought, which made it more than attractive to develop law-responsive approaches for 21st-century tendencies in Islamic law. The paper's objectives were to identify commonalities and differences between Zaidiyah and Ja'fariyah perspectives on Maqāṣid and to test how these differences contribute to the solution of contemporary issues, including sex- and law-gender equality, and law pluralism. The research employed a comparative qualitative design overall, with a textual-contextual analysis approach, conducting deep and critical analysis of classical material, as well as a thematic one, to track patterns of Maqāṣid interpretation. The results include the fact that Zaidiyah adopted a systemic rational-contextual approach to Maqāṣid based on al-maslahah al-‘āmmah and Ja'fariyah – an imamah-centric approach via al-taqiyyah al-ijtihādiyyah. The study also concludes that the synthesis of these approaches is effective in providing a methodology for Islamic law.